A study of Representation and Mathematical Problem Solving for Mathayomsuksa I students - suksawat, yatawee; Thipchart, yuthapong (Journal for Developing the Social and Community, 2024)
The purposes of this study were to (1) study the representation of Mathayomsuksa 1 students, (2) study the mathematical problem solving of Mathayomsuksa 1 students, (3) study the relation between the representation and Mathematical problems solving for Mathayomsuksa 1 students. With a purposive sampling, purposive sampling were 80 students from the seven grade class had two classes was 1/6 and 1/8, Sarakham Pittayakhom School, Mueang Maha Sarakham, Maha Sarakham province, Under the jurisdiction of the Secondary Educational Service Area Office 26. Research tools were a representation test, a mathematical problem solving test, and an interview form of solving mathematical problems. Statistics for research were percentage, average, standard deviation, pearson correlation coefficient and a case study method. Data were presented through descriptive analysis. The results of the study were as follow: (1) the level of representation of most Mathayomsuksa 1 students was at a moderate level, representing 52.50 percent, followed by a low level, it is 33.75 percent and is at a high level, represented as 13.75 percent (2) The mathematical problem solving of the Mathayomsuksa 1 students mostly at mathematical problem solving is in fairly level, representing 38.75 percent, and (3) the relation between representation and mathematical problem solving is a high level. With a correlation coefficient of .814 and from the interviews, it was found that students at a high level be confident in answering questions and solving problems in a sequential and logical manner. Students who are in the middle level Have some confidence in answering questions. Problems are solved sequentially and logically but cannot explain thinking and problem solving. students at a low level Lack of confidence in answering questions There is no sequential and logical solution to the problem. Some people know how to solve problems but cannot use computational thinking skills to solve them.The purposes of this study were to (1) study the representation of Mathayomsuksa 1 students, (2) study the mathematical problem solving of Mathayomsuksa 1 students, (3) study the relation between the representation and Mathematical problems solving for Mathayomsuksa 1 students. With a purposive sampling, purposive sampling were 80 students from the seven grade class had two classes was 1/6 and 1/8, Sarakham Pittayakhom School, Mueang Maha Sarakham, Maha Sarakham province, Under the jurisdiction of the Secondary Educational Service Area Office 26. Research tools were a representation test, a mathematical problem solving test, and an interview form of solving mathematical problems. Statistics for research were percentage, average, standard deviation, pearson correlation coefficient and a case study method. Data were presented through descriptive analysis. The results of the study were as follow: (1) the level of representation of most Mathayomsuksa 1 students was at a moderate level, representing 52.50 percent, followed by a low level, it is 33.75 percent and is at a high level, represented as 13.75 percent (2) The mathematical problem solving of the Mathayomsuksa 1 students mostly at mathematical problem solving is in fairly level, representing 38.75 percent, and (3) the relation between representation and mathematical problem solving is a high level. With a correlation coefficient of .814 and from the interviews, it was found that students at a high level be confident in answering questions and solving problems in a sequential and logical manner. Students who are in the middle level Have some confidence in answering questions. Problems are solved sequentially and logically but cannot explain thinking and problem solving. students at a low level Lack of confidence in answering questions There is no sequential and logical solution to the problem. Some people know how to solve problems but cannot use computational thinking skills to solve them.